Lessons in art : art, education, and modes of instruction since 1500 = Lessen in kunst : kunst, onderwijs en vormen van instructie sinds 1500 - Jorink, Eric; Jorink, Eric; Lehmann, Ann-Sophie; Lehmann, Ann-Sophie; Ramakers, Bart; Ramakers, Bart (Nederlands kunsthistorisch jaarboek, 2019)
Why, how, to whom and by whom was art taught? 'Lessons in Art' (Netherlands Yearbook for History of Art, Vol 68) provides new answers to these questions by addressing the relation between art and education in the Netherlands from 1500 to the 1970s. The authors gathered in this volume consider the practical education of artists within a wide societal context. They present new ways of looking at teaching materials and methods and show how art was employed as a powerful teaching aid. From early-modernity to the present, education, it appears, fuels the production and perception of art